2014
DOI: 10.1097/aci.0000000000000088
|View full text |Cite
|
Sign up to set email alerts
|

T helper subsets in allergic eye disease

Abstract: Purpose of review Ocular allergy is an IgE-mediated disease that results in inflammation of the conjunctiva and, in more severe cases, the cornea. This is driven by an immediate hypersensitivity response via mast cells, followed by a late phase response mediated by eosinophils—both of which are indeed dependent on T helper (Th) lymphocyte activity. Here we provide an update on Th subsets (Th1, Th2, Th17, T regulatory (Treg) and their relevance in ocular allergy. Recent findings Recent evidence in ocular alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 117 publications
1
12
0
Order By: Relevance
“…Upon migration to the lymph node, these dendritic cells initiate an effector Th1/Th17 T-cell response that further fuels this vicious cycle at the ocular surface by contributing to epithelial cell damage. and giant papillary conjunctivitis) differ in the contribution of IgE-mediated and non-IgE-mediated immune reactions in their pathogenesis, 93 but they share the hallmark Th2 adaptive immune response to an otherwise harmless antigen that typifies allergic disease. In other words, an allergic reaction at a mucosal surface is in fact a clinical example of the breakdown of mucosal tolerance to one or more specific antigens.…”
Section: Ocular Allergymentioning
confidence: 99%
“…Upon migration to the lymph node, these dendritic cells initiate an effector Th1/Th17 T-cell response that further fuels this vicious cycle at the ocular surface by contributing to epithelial cell damage. and giant papillary conjunctivitis) differ in the contribution of IgE-mediated and non-IgE-mediated immune reactions in their pathogenesis, 93 but they share the hallmark Th2 adaptive immune response to an otherwise harmless antigen that typifies allergic disease. In other words, an allergic reaction at a mucosal surface is in fact a clinical example of the breakdown of mucosal tolerance to one or more specific antigens.…”
Section: Ocular Allergymentioning
confidence: 99%
“…34 However, the role of Th17 in ocular allergy is poorly understood. 27 We hypothesised that the progression of T1DM, which was defined in this study as a yearly increase in aDCSI score, is positively correlated with the risk of AC development. We found a significant trend in increase of AC risk with the progression of T1DM (p for trend <0.001).…”
Section: Open Accessmentioning
confidence: 99%
“…Additional insights into the roles of Tregs and B lymphocytes in both disorders are required. [25][26][27] The control of ocular allergies has been suggested to involve a balance between Tregs and pathogenic T cells, and changes in Treg frequencies have been reported in patients with AC. One study showed that, upon challenge with the Dermatophagoides pteronyssinus allergen, patients with PAC exhibited a higher frequency of CD4+CD25+ cells than healthy controls.…”
Section: Open Accessmentioning
confidence: 99%
“…Whereas conventional animal models of eye allergy are typically mild and self-limiting in nature 6 , a more recently established system in mice, referred to as the allergic eye disease (AED) model 7,8 , is considered to be akin to chronic/severe forms. Disease in this model is evidenced by a robust eosinophil presence 9 , blepharitis 10 conjunctival scarring 1113 , thick mucoid discharge, and meibomian gland dysfunction 14 which are consistent with features of chronic disease 15 The AED model is important because the pathobiology of chronic eye allergy is understudied and renewed research efforts are needed to better understand the pathobiology and help reduce disease burden.…”
Section: Introductionmentioning
confidence: 96%